Improvement of Gasless Laparoscopic Single-Site Lifting and Use in Surgery for Endometrial Carcinoma - Bingbing Zhao; Xinqiu Lu; Xuli Gan; Zhijun Yang; Li Li; Jieqing Zhang (Clinical and Experimental Obstetrics & Gynecology)
Background: The operative field in gasless surgery is limited, and it is difficult to adequately expose the operative field when compared to the use of gas surgery. Gasless laparoscopic single-site (GLESS) is difficult to apply to endometrial cancer surgery. The aim of this study is to investigate the improvement in GLESS lifting style for use in surgery for endometrial cancer as well as to compare the outcome of different surgical approaches in endometrial cancer. Methods: A tissue retractor is added to the routine step of GLESS to lift the abdominal wall. The lateral umbilical ligament is exposed, a 2-0 buckwheat thread is passed through the lateral umbilical ligament and abdominal wall in order to lift the umbilical ligament. We measured the changes of space length or height in different dimensions of the improved GLESS approach. Also, we measured the vertical height from the upper edge of the umbilical site to the abdominal cavity, the length from the lower edge of the umbilical site to the right Michaelis point, the height from the bottom of the uterus to the peritoneal cavity of the anterior abdominal wall, and the length from the lateral umbilical ligament to the ipsilateral psoas major muscle. We analyzed the differences in procedures in 177 cases of endometrial carcinoma. We collected data on operative time, hemoglobin change, number of lymph nodes removed, postoperative recovery time and postoperative complications for open surgery, multi site laparoscopic surgery, single site laparoscopic surgery and gasless laparoscopic single-site surgery. Results: The vertical height from the upper edge of the umbilical foramen to the abdominal cavity (4.395 ± 1.593 cm vs. 7.418 ± 1.626 cm, p < 0.001), the length from the lower edge of the umbilical foramen to the right Michaelis point (9.850 ± 2.089 cm vs. 12.795 ± 2.094 cm, p < 0.001), the height from the bottom of the uterus to the peritoneal cavity of the anterior abdominal wall (6.900 ± 1.052 cm vs. 9.827 ± 1.366 cm, p < 0.001), and the length from the lateral umbilical ligament to the ipsilateral psoas major muscle and iliac vessels were measured (2.345 ± 0.515 cm vs. 4.318 ± 0.558 cm, p < 0.001) and showed improvement with GLESS. Also, the operative visualization increased significantly with GLESS. No significant difference was observed in operative time (p = 0.670), hemoglobin change (p = 0.065), number of lymph nodes removed (p = 0.179), postoperative recovery time (p = 0.331), or postoperative complications (p = 0.442) in cases of endometrial cancer utilizing GLESS. Conclusions: The use of GLESS can increase surgical exposure. This method of suspending the umbilical ligament through abdominal silk thread can increase exposure of the anatomical structure of the obturator position. The application of GLESS as the procedure for endometrial cancer is safe and feasible.